2013
DOI: 10.1128/mcb.00217-13
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin 2 and AMPK Connect Hyperglycemia to Nox4-Dependent Endothelial Nitric Oxide Synthase Uncoupling and Matrix Protein Expression

Abstract: Mesangial matrix accumulation is an early feature of glomerular pathology in diabetes. Oxidative stress plays a critical role in hyperglycemia-induced glomerular injury. Here, we demonstrate that, in glomerular mesangial cells (MCs), endothelial nitric oxide synthase (eNOS) is uncoupled upon exposure to high glucose (HG), with enhanced generation of reactive oxygen species (ROS) and decreased production of nitric oxide. Peroxynitrite mediates the effects of HG on eNOS dysfunction. HG upregulates Nox4 protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 72 publications
6
122
0
Order By: Relevance
“…Reports show that sestrin2 activates AMPK through upstream kinase LKB1 (liver kinase B1) (54,55). AMPK is proposed to be a mediator of benefits in longevity and calorie restriction (56,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports show that sestrin2 activates AMPK through upstream kinase LKB1 (liver kinase B1) (54,55). AMPK is proposed to be a mediator of benefits in longevity and calorie restriction (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…There are two separate pathways that contribute to regulation of mTOR by sestrins, the AMPK-TSC2 (tumor suppressor proteins that are associated with an autosomal dominant disorder known as tuberous sclerosis complex) axis and Rag GTPase (62). The AMPK-TSC2 pathway has been shown to function in ionizing radiation in breast cancer, hyperglycemia-induced glomerular injury, and quercetin-induced apoptosis, while the latter pathway recently was elucidated to function in sensing amino acid and mTOR lysosomal localization (54,55). Although both pathways might function simultaneously, the present study showed that, in an in vitro rotenone PD model, sestrin2 could regulate autophagy through activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the vasculature or the kidney, Nox4-mediated superoxide production was detected in other systems (28,33,41). We have previously shown that NADPH oxidase Nox4 plays an important role in podocyte injury (16)(17)(18)(19).…”
Section: Innovationmentioning
confidence: 99%
“…In this study, OVE26 mice were treated with phosphorothioate sense (S) or (AS) oligonucleotides targeting Rictor (90 ng$g body wt -1 $day -1 for 5 weeks), administered subcutaneously by an ALZET osmotic minipump (Alza, Palo Alto, CA). Control FVB mice were treated with vehicle (19). Because of their nuclease stability and relative ease of synthesis, the phosphorothioates are the most widely studied oligonucleotides; they are highly soluble and have excellent AS activity (12).…”
Section: Mtorc2 Signaling In Diabetic Nephropathymentioning
confidence: 99%
“…The ability of the AMP-activated protein kinase (AMPK) to detect metabolic alterations and to modulate cellular bioenergetic and redox states appears to contribute to mortality and organ dysfunction in sepsis as well as to recov ery from this life-threatening condition (24)(25)(26). AMPK is a heterotrimer that consists of one catalytic α and two regu latory β and γ subunits (27).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%